Ayurveda Management of Shweta Pradara (Leucorrhoea) - A Case Study. - Meher, Krishna; Meher, Sudeshna (International Research Journal of Ayurveda & Yoga, 2023)
The greatest method to prevent sickness is to adopt healthy behaviours. But nowadays, healthy living is seldom ever practised due to the complexity of a woman’s everyday existence. A woman’s vaginal health is just as vital as her general health. A lady in good health is a guarantee of a long life. Every stage and period of a woman’s life involves both physical and psychological transitions. She also has a dual obligation to take care of her family and her career. She must thus be in great physical and mental condition. A healthy yoni is essential to a woman’s ability to live a safe, healthy, and confident life. Inflammation of the vagina can be brought on by an infection or a shift in the usual ratio of yeast and bacteria in the vagina. Shweta pradara is a bothersome symptom that can be a complication in various disorders. Shweta Pradara is a symptom, not a disease, hence its etiopathogenesis would coincide with that of the primary illness. It is possible to say that it is an Apana Vayu regional Kaphaja disease. White discharge can also result from infections in the uterus and vagina caused by certain organisms. Shamana Chikitsa and Yoni Prakshalana treated a female patient with Shweta Pradara. With the foregoing regimen, she had significant symptom alleviation.